Internalization of Religious and Social Character through the Islamic Building and Character Building Programs (A Case Study at Madrasah Ibtidaiyah International Sabilillah Sampang) - Syari'ah, Atiris; Maimun, Agus; Marno, Marno (LP2M STIT Palapa Nusantara, 2025)
In response to the growing prevalence of moral degradation within educational environments, there is an urgent need for effective solutions. This study focuses on exploring the values embedded within the Islamic Building and Character Building programs, the models of value internalization, and the implications of religious and social character development for students. A qualitative approach with a case study design was employed to narrow the broad research scope into a specific, in-depth area of investigation. Data were collected through in-depth interviews, observations, and document analysis. Data analysis was carried out through data display, condensation, and conclusion drawing. The findings reveal that the values internalized through the Islamic Building and Character Building programs play a significant role in reinforcing students’ religious character and social awareness. The Islamic Building program encompasses values such as faith, worship, morality, steadfastness (istiqamah), and brotherhood (ukhuwah), while the Character Building program emphasizes leadership, empathy, creativity and innovation, collaboration, and responsibility. A variety of activities were designed to foster a conducive learning environment, including the implementation of the 5S routine (smile, greet, salute, polite, and courtesy), recitation of prayers before and after lessons, collective performance of Duha and Dhuhr prayers, a Qur’an memorization (tahfiz) program, the internalization of a sense of shame towards misconduct, and character development led by homeroom teachers. The internalization programs positively impacted students’ character, as evidenced by greater consistency in religious observances, stronger adherence to school rules, improved discipline, and a heightened sense of social responsibility.